Eco-design and sustainability in packaging: a survey - Monteiro, J. (2020)
According to “The 2030 Agenda for Sustainable Development” of the United Nations, there are seventeen goals essential for the World Sustainable Development. One of these goals has direct implication for the industrial sector – ensure sustainable consumption and production patterns. In a world where globalization is more and more present, packaging emerges as a link between all points around the world, allowing transporting and commercializing products on a global level, from producers to consumers. Therefore, it is necessary to study how the packaging industry is adapting itself to the increasing demands of the markets, while complying with the global environmental requirements and sustainable goals established by international organizations. Accordingly, this paper aims to analyse precisely this industry, intending to understand how the theme of Ecodesign and sustainability are faced by packaging manufacturers, and what are the key-factors associated to the success of their implementation in the companies. Characterization of the industry is also presented, defining how companies should organize and prepare themselves in order to have a diminishing environmental impact, a raw-materials sustainability policy and consider environmental aspects through the packaging’s life cycle – Eco-design.